The effect of care worker communication style on the communicative behaviour of care home residents with dementia: a mixed methods study - Gray, Miriam (2014)
Previous research into communication between care workers and care home residents with dementia has not utilised the experience of healthcare professionals who work with people with dementia on a daily basis. Previous research mostly consists of observational studies and the assessment of care worker training programmes. No study has yet attempted to establish the efficacy of isolated communication strategies, recommended by healthcare professionals, and administered by care workers within a residential care setting. This thesis first presents the thematic analysis of 16 semi-structured interviews with healthcare professionals who have experience of working with people with dementia. The participants discuss the personal characteristics required in a healthcare professional to facilitate communication, the verbal and non-verbal strategies they use and the organisational factors which can impact the delivery of communication as desired.